Marketing Postulates - Páramo Morales , Dagoberto (Universidad Francisco de Paula Santander, 2014)
This paper proposes a new and revolutionary way to approach marketing. Breaking the marketing mix traditional and popular view, it is presented what might be called the essence of marketing. Based on a thorough literature and historical review eleven principles have been presented getting a new impetus to current marketing. Postulates that to acquire significant relevance must be seen and adapted to the specific conditions of each context and not as principles chiseled in stone. It is due to its own ability to be adapted to the environment what has become them more transcendent in organizations which are already being applied.